Dynamische Rekonfigurationsmethodik für zuverlässige, echtzeitfähige Eingebettete Systeme in Automotive - Oszwald, Florian (Steinbuch Series on Advances in Information Technology, 2021)
Currently, dynamically reconfigurable systems are not used in automotive and there is no process model for their development. The focus of this dissertation is to explore methods and approaches for the development of such systems. One major architectural driver is autonomous driving, another is functional high integration on central computing platforms. Taking these into account, dynamic reconfiguration is classified and explored.